1997
DOI: 10.1002/(sici)1096-8644(199712)104:4<471::aid-ajpa4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor ecology ofLepilemur edwardsi andAvahi occidentalis

Abstract: A well-known principle holds that where food supply is limited, two sympatric species with the same diet, morphology, and behavior will compete, leading to exclusion of one species or differentiation of their ecological niches. Avahi occidentalis and Lepilemur edwardsi are two saltatory, nocturnal folivorous lemurs of similar body size which live sympatrically over much of their range and may often be seen feeding in the same trees. We report a study of their locomotor behavior, carried out in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Specifically, compliant substrates absorb some of the mechanical work that would be otherwise employed to redirect and accelerate the CoM during steady locomotion, and compromise stability by undermining the animal's ability to estimate body orientation (MacLellan and Patla, 2006). Previous research has shown that increasing branch compliance significantly compromises the locomotor performance of leaping primates (Crompton et al, 1993;Demes et al, 1995;Warren and Crompton, 1997;Walker, 2005;Channon et al, 2011) and lizards (Gilman et al, 2012;Gilman and Irschick, 2013), and necessitates numerous postural and locomotor adjustments in orangutans (Thorpe et al, 2009;Myatt and Thorpe, 2011). However, relative to the breadth of research on the effects of substrate diameter, studies of how perch compliance affects quadrupedal gait mechanics are sparse (but see Stevens et al, 2001;GosselinIldari, 2010).…”
Section: Influence Of Substrate Compliance On Gait Kinematicsmentioning
confidence: 99%
“…Specifically, compliant substrates absorb some of the mechanical work that would be otherwise employed to redirect and accelerate the CoM during steady locomotion, and compromise stability by undermining the animal's ability to estimate body orientation (MacLellan and Patla, 2006). Previous research has shown that increasing branch compliance significantly compromises the locomotor performance of leaping primates (Crompton et al, 1993;Demes et al, 1995;Warren and Crompton, 1997;Walker, 2005;Channon et al, 2011) and lizards (Gilman et al, 2012;Gilman and Irschick, 2013), and necessitates numerous postural and locomotor adjustments in orangutans (Thorpe et al, 2009;Myatt and Thorpe, 2011). However, relative to the breadth of research on the effects of substrate diameter, studies of how perch compliance affects quadrupedal gait mechanics are sparse (but see Stevens et al, 2001;GosselinIldari, 2010).…”
Section: Influence Of Substrate Compliance On Gait Kinematicsmentioning
confidence: 99%
“…Avahis are particularly intriguing in this context because their body mass is at the lower limits for primate folivores (750-1400 g: Kay 1984;Lehman 2007), they are nocturnal (Norscia and Borgognini-Tarli 2008) and thus active at a time when low ambient temperature possibly increases metabolic requirements to remain normothermal (Willmer et al 2000), and their locomotion is energetically expensive (vertical leaping; Warren and Crompton 1997). Like all indriids, Avahi spp.…”
Section: Malagasy Folivoresmentioning
confidence: 99%
“…Energy saving might also explain the relatively small home ranges of sportive lemurs-about 1 ha for L. edwardsi (see Albignac 1981;Warren and Crompton 1997) and L. ruficaudatus (Zinner et al 2003), and 0.18 ha for female and 0.33 ha for male L. leucopus (see Dröscher and Kappeler 2013). The much smaller grey mouse lemur (Microcebus murinus), with its broad diet, has similar home ranges of 0.7-1.6 ha for females and 2.8-4.8 ha for males in dry deciduous forest (Eberle and Kappeler 2004;Lahann 2008;Radespiel 2000).…”
Section: Observation Time (H)mentioning
confidence: 99%